2022
DOI: 10.1021/acssuschemeng.2c05143
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Capacity and Rapid Selective Recycling of Gold Ions by Organic Intercalated and Exfoliated Few-Layer Ti3C2Tx Nanosheets

Abstract: For the sustainable development of the ecological environment in gold recycling, it is urgently desired to develop a more efficient and highly selective process for gold ions from ewaste or mineral lixivium. As a kind of emerging two-dimensional nanomaterials, Ti 3 C 2 T x has emerged as a rapidly developing novel water treatment material. Herein, the preparation of few-layer Ti 3 C 2 T x nanosheets and their performance for recycling of gold ions were studied. Notably, it exhibits an impressive capacity of 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…The higher ζ-potential of PCN-224 in light led to relatively stronger repulsion to positive nonprecious metal ions, thus showing enhanced selectivity. In summary, we found that visible light largely promoted the Au recovery performance of PCN-224 and made it superior to other materials in terms of recovery capacity ( q max ) and selectivity ( K d ), including UiO-66, COFs, polymers, ,,, and 2D materials ,, (Figure S9).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The higher ζ-potential of PCN-224 in light led to relatively stronger repulsion to positive nonprecious metal ions, thus showing enhanced selectivity. In summary, we found that visible light largely promoted the Au recovery performance of PCN-224 and made it superior to other materials in terms of recovery capacity ( q max ) and selectivity ( K d ), including UiO-66, COFs, polymers, ,,, and 2D materials ,, (Figure S9).…”
Section: Resultsmentioning
confidence: 90%
“…We also noted that visible light enhanced the selectivity of Au by both increasing the recovery of Au(III) and decreasing the uptake of nonprecious metals. Under light irradiation, the uptake of Zn and made it superior to other materials in terms of recovery capacity (q max ) and selectivity (K d ), including UiO-66, 57 COFs, 58−61 polymers, 37,38,62,63 and 2D materials 33,64,65 (Figure S9).…”
Section: ■ Introductionmentioning
confidence: 99%